Optimizing LMS CANVAS for Interactive Online Learning Perceived by the Students - Santiana Santiana; Dea Silvani; Ruslan Ruslan (Journal of English Education and Teaching, 2021)
Recently, technology has been an integral part of education. Teachers must use technology into their teaching practices in order to adapt to society's digital revolution. One of the strategies that can be implemented by the teachers is utilizing Canvas as one of Learning Management Systems (henceforth LMS) in their course. This study aims to investigate the students’ perception towards the use of Canvas to promote interactive online learning. Implementing case study as the research design, this study involved 77 students as the participants, and used both questionnaire and semi-structured interview to collect the data. In this study, the quantitative data were analyzed using descriptive statistics, while the qualitative data were analyzed using thematic analysis. The findings of this study revealed that students accessed Canvas ranging for less than 1 hour to more than 2 hours in a week.  They accessed it mostly to join some learning activities designed by the teacher, including reading the learning modules, joining online discussion, and doing the assignments given by the teachers. They also believe that during the online learning, Canvas is an easy-to-use LMS, and it provides a lot of features that help them learning. Besides, they also agree that Canvas is effective to provide them the opportunity have an interactive learning experience. In addition, they also perceived that using Canvas motivated them, and make the learning process more interesting. Therefore, teachers can optimize various features provided by Canvas to make the teaching and learning process in online setting become more interactive, interesting, and effective.